Penerapan Target Costing Sebagai Upaya Pengendalian Biaya Produksi Dalam Meningkatkan Laba - Oktalina, Gayatria; Andriyani, Friska; Widayanti, Agnisa (P3M Politeknik Negeri Bengkalis, 2024)
This study aims to determine the application of target cost to control production costs and increase the profitability of Ninecake Cake Shop. This research method uses a qualitative approach, namely by collecting primary data sources in the form of interview results which are then analyzed using qualitative descriptive techniques. The subjects of this study were the owners of Ninecake Cake Shop. The results of the study indicate that the application of target cost is very effective in controlling and saving production costs, as well as helping business owners in setting expected profit targets so that strategic decision making for management can contribute to business growth. Before implementing the target costing method, the company earned a profit of 20% from the sale of roll cakes and cupcakes, according to calculations. It turned out that the shop was able to meet a higher profit target than before, which was 29% for the sale of roll cakes and cupcakes, after using the target cost approach through value engineering and efficient production costs. The findings of this study also show that the application of target costing is very effective in controlling and saving production costs, as well as helping business owners to achieve expected profit targets so that strategic decision making for management can contribute to business growth.